Inflammatory cytokines in pediatric obstructive sleep apnea. Issue 41 (October 2016) - Huang, Yu-Shu; Guilleminault, Christian; Hwang, Fang-Ming; Cheng, Chuan; Lin, Cheng-Hui; Li, Hsueh-Yu; Lee, Li-Ang
Abstract : Abstract: Pediatric obstructive sleep apnea (OSA) is associated with chronic systemic inflammation and with cognitive impairments. This study aimed to investigate the status of proinflammatory cytokines, particularly interleukin 17 (IL-17) and interleukin 23 (IL-23) and cognition in pediatric OSA. Controls and OSA children participated in the study. Exclusion criteria were adenotonsillectomy, heart, neurological and severe psychiatric diseases, craniofacial syndromes, and obesity. Polysomnogram was followed by serum testing for inflammatory markers and neurocognitive tests such as continuous performance task (CPT) and Wisconsin card sorting test, questionnaires, analyses of plasma high-sensitivity C-reactive protein (HS-CRP), tumor necrosis factor alpha (TNF-α), interleukin 1 (IL-1), interleukin 6 (IL-6), IL-17, and IL-23. Seventy-nine, 4 to 12-year-old subjects in 2 groups ended the study: 47 nonobese OSA children (mean age = 7.84 ± 0.56 years, body mass index [BMI] = 16.95 ± 0.47 kg/m 2, BMI z-score = 0.15 ± 0.21, and mean apnea–hypopnea index [AHI] = 9.13 ± 1.67 events/h) and 32 healthy control children (mean age = 7.02 ± 0.65 years, with BMI = 16.55 ± 0.58 kg/m 2, BMI z-score = −0.12 ± 0.27, and mean AHI = 0.41 ± 0.07 event/h) were enrolled. Serum cytokine analyses showed significantly higher levels of HS-CRP, IL-17, and IL-23 in OSA children ( P = 0.002, P = 0.024, and P = 0.047). Regression test showed significant influence of HS-CRP, TNF-α, IL-6, IL-17, and specifically IL-23, with the continuous performance test and Wisconsin card sorting test. OSA children have abnormal levels of IL-17, an interleukin related to T helper 17 cells, a T helper cell involved in development of autoimmunity and inflammation. This high expression level may contribute to the complications of pediatric OSA; we also found a significant influence of inflammatory cytokines, particularly IL-23, on abnormal neurocognitive testing.